Educational interventions to reduce prescribing errors. Issue 4 (15th January 2008) - Conroy, S; North, C; Fox, T; Haines, L; Planner, C; Erskine, P; Wong, I; Sammons, H
Abstract : Objective: Little is known about teaching paediatricians to prescribe or about assessing their competency. This study aimed to identify educational interventions to reduce dose calculation errors. Design: Literature review, a questionnaire survey of paediatric healthcare professionals, observation and interviews were performed. Results: Literature review identified one paper describing an in-service test for medical trainees. 319/559 questionnaires were returned (57%). 34 mentioned educational interventions, 15 centres provided further information on teaching and assessment methods and 13 provided presentations, usually at doctors' induction. Many interventions had a similar format, including describing differences from adult prescribing, common errors and how to calculate doses. Paediatric clinical pharmacists play a significant role in delivering training and competency assessment. Conclusion: Teaching of paediatric prescribing takes place mostly in the format of lectures during doctors' induction. Few centres assess competency and no validated tool exists. There has been little evaluation of the impact of teaching on competency to prescribe.